1993
DOI: 10.1084/jem.178.4.1447
|View full text |Cite
|
Sign up to set email alerts
|

JL1, a novel differentiation antigen of human cortical thymocyte.

Abstract: SummaryExpression of a novel thymocyte differentiation antigen, JL1, defined by a monodonal antibody (mAb) developed against human thymocytes showed a specificity for stage II double positive (CD4+CD8 +) human cortical thymocytes. This antigen was not expressed at detectable levels on medullary thymocytes, mature peripheral leukocytes, bone marrow cells or on other types of tissues elsewhere in the human body. Immunohistologic analysis revealed that JL1 had a clear pattern of distribution on cortical thymocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…These findings, together with the fact that JL1 is not expressed on mature peripheral monocytes or granulocytes, 17 suggest that JL1 antigen is expressed during the later maturation process in the case of myelomonocytic hematopoiesis. Taken together, these results showed that JL1 antigen is specifically expressed at the earlier stages of B and T cell lineages as well as at the later stage of myelomonocytic cells in BM but not on pluripotent stem cells or not on mature peripheral blood cells ( Figure 6).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These findings, together with the fact that JL1 is not expressed on mature peripheral monocytes or granulocytes, 17 suggest that JL1 antigen is expressed during the later maturation process in the case of myelomonocytic hematopoiesis. Taken together, these results showed that JL1 antigen is specifically expressed at the earlier stages of B and T cell lineages as well as at the later stage of myelomonocytic cells in BM but not on pluripotent stem cells or not on mature peripheral blood cells ( Figure 6).…”
Section: Discussionmentioning
confidence: 80%
“…Collectively, JL1 is likely to be firstly expressed from common lymphoid progenitors and widely distributed during lymphoid ontogenesis, and to be down-regulated at the time of the final maturation process because JL1 is not expressed on peripheral mature T or B cells. 17 These suggest a possible role of the down-regulation of JL1 molecule in the completion of lymphocyte maturation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…16 The ascitic form of anti-JL1 mAb was produced after injection of hybridoma cells into pristane-pretreated Balb/c mice. The antibody was purified using Qsepharose (Pharmacia) and hydroxylapatite (Bio-gel HTP gel; Pharmacia) column chromatography.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…16 Briefly, the cells were surface-radiolabeled with 125 I using lactoperoxidase-catalyzed iodination, and were lysed in the buffer (50 mM Tris-HCl, pH 7.4, 50 mM EDTA, 1 mM PMSF) containing 1% (v/v) Nonidet P-40. After preclearing by mixing the lysate with irrelevant immunoglobulin-conjugated protein A-sepharose CL-4B beads, immunoprecipitations were done by mixing lysate with anti-JL1 mAb-conjugated protein A-sepharose CL-4B beads.…”
Section: Immunoprecipitationmentioning
confidence: 99%